2018
DOI: 10.1302/0301-620x.100b6.bjj-2017-1295.r1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in femoral trochlear morphology following surgical correction of recurrent patellar dislocation associated with trochlear dysplasia in children

Abstract: The femoral trochlear morphology can be improved by early (before epiphyseal closure) surgical correction in children with recurrent patellar dislocation associated with femoral trochlear dysplasia. Cite this article: Bone Joint J 2018;100-B:811-21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 57 publications
7
62
0
Order By: Relevance
“…In the study group (Table 2), the patellar tilt angle (28.4 ± 7.1°) and congruence angle (22.8 ± 6.3°) before surgery decreased signi cantly at the last follow-up (patellar tilt angle: 10.7 ± 2.3°; congruence angle: 8.4 ± 2.6°). The sulcus angle in the study group (148.2 ± 7.2°) was signi cantly different from that at the last follow-up(144.1 ± 5.4°), which was consistent with the study by Fu [18].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the study group (Table 2), the patellar tilt angle (28.4 ± 7.1°) and congruence angle (22.8 ± 6.3°) before surgery decreased signi cantly at the last follow-up (patellar tilt angle: 10.7 ± 2.3°; congruence angle: 8.4 ± 2.6°). The sulcus angle in the study group (148.2 ± 7.2°) was signi cantly different from that at the last follow-up(144.1 ± 5.4°), which was consistent with the study by Fu [18].…”
Section: Resultssupporting
confidence: 90%
“…Benoit et al [17] reported that children with recurrent patellar dislocation had a statistically signi cant improvement in the femoral sulcus angle after patellar stabilization procedure. Fu et al [18] found that the femoral trochlear morphology can be improved with lower trochlear groove angle and higher trochlear groove depth by early surgical correction in children with recurrent patellar dislocation associated with femoral trochlear dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the patella and femoral trochlea dysplasia can occur after patella dislocation [14,15,16]. This study and the study by Fu [18] showed signi cant morphological alteration of patella and femoral trochlea after surgical correction in the children with recurrent patella dislocation. So the development of the patella and femoral trochlea was thought to be effected on both congenital factors and acquired factors, especially the engagement between patella and femoral trochlea.…”
Section: Discussionsupporting
confidence: 51%
“…Combined with the previous study [14,15,16,18], the normal patella position with femoral trochlea is important for the patellofemoral development. Patellar and femoral trochlear dysplasia can occur after patella dislocation [14,15].…”
Section: Discussionmentioning
confidence: 74%
“…Animal studies have found that abnormal mechanical stress (patellar subluxation or instability) may lead to patellofemoral TD and patellofemoral osteoarthritis. However, both animal and clinical investigations have revealed that early restoration of the patella can minimize such dysplasia. Therefore, the development of the femoral trochlea may not only be determined by genetics, but may also be altered by acquired conditions.…”
Section: Discussionmentioning
confidence: 99%